Analisis Pola Distribusi dan Keanekaragaman Komunitas Biotik di Lima Kecamatan Kabupaten Majene, Sulawesi Barat dengan Metode Relevé - Ratna Sari (Biocaster : Jurnal Kajian Biologi, 2025)
Indonesia is known as one of the mega-biodiversity countries in the world, because it has a very high level of biodiversity, which is influenced by geographical conditions, tropical climate, and the diversity of ecosystems spread across various islands. This study aims to analyze the diversity of flora and fauna communities using the Relevé method in five sub-districts in Majene Regency, West Sulawesi Province, namely Sendana, East Banggae, Banggae, Tammerodo Sendana, and Pamboang Districts. The relevé method was applied with a multi-level approach through three plot sizes, namely 1×1 m², 3×3 m², and 5×5 m² to observe the influence of area area on the number of species found. The results of the observations showed that the increase in the area of the plot was directly proportional to the number of species identified. In plots measuring 1×1 m², the lowest average number of species was found, while in plots measuring 5×5 m², the highest number of species was found. The results of this study show that there is a pattern of positive relationships between area area and species richness which reflects the level of environmental heterogeneity and ecosystem complexity in the research area. The Relevé curve shows an inlinear trend of increasing the number of species with a tendency to reach saturation points on the widest plot, indicating that most species are already represented in that area. These findings confirm that the Relevé method is an effective approach in studying the structure and composition of biotic communities, especially in areas with diverse ecological conditions such as Majene Regency. The results of the research are expected to be the basis for efforts to manage and conserve local biodiversity, as well as provide an overview of the ecological potential in the five sub-districts studied.